2021
DOI: 10.1111/medu.14535
|View full text |Cite
|
Sign up to set email alerts
|

You never forget your first? Impact of interview timing on institutional rank order

Abstract: Objective To analyze the impact of interview date on the applicant rank for Neurology residencies in the United States. Methods A multi‐institutional retrospective review of interview dates and applicant rank list data for the National Resident Matching Program (NRMP) was conducted for five Neurology programs, totaling 1932 interviewed applicants over a combined total of 31 interview years. For each candidate, the interview date and applicant rank were abstracted along with the total number of interviews for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Additionally, Hanrahan et al [29] reported that the primacy bias merited further evaluation in medical specialties.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Hanrahan et al [29] reported that the primacy bias merited further evaluation in medical specialties.…”
Section: Discussionmentioning
confidence: 99%
“…As part of the selection process, program signals are only appropriate for use in interview selection because applicants may change their program preferences after completing interviews. 12 Given that application volume varies by program, we expected a nonuniform distribution of signals across programs. 10 Therefore, the primary objectives of this study were to explore the distribution of program signals sent to programs by applicants and to investigate whether there were trends in how program and applicant characteristics related to signal distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Programs consider a wide range of factors that impact an applicants’ ability to thrive in residency, including letters of recommendation, personal statements, and proximity to social support networks or previous experience living in a similar environment or level of development (e.g., urban vs rural). As part of the selection process, program signals are only appropriate for use in interview selection because applicants may change their program preferences after completing interviews 12 . Given that application volume varies by program, we expected a nonuniform distribution of signals across programs 10 .…”
mentioning
confidence: 99%
“…We pause at this juncture to emphasize again that the sequential and relative characteristics of the evaluation problems are not specific to sports competitions, but apply to several other applications where sequential bias has been empirically observed. These include music competitions [16,20,1], hiring [48], grading [47], residency matching at medical schools [13,23] and grant review [51]. Much like sports competitions, these applications are often single-shot and high-stakes [20], and reducing sequential bias in these tasks is an important problem.…”
Section: Introductionmentioning
confidence: 99%